2023
DOI: 10.3389/fneur.2023.1144481
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge and awareness of stroke in the Iraqi population: a cross-sectional study

Abstract: IntroductionStroke is a highly prevalent condition with high rates of death and disability in Iraq and around the world. Knowledge of stroke and its associated risk factors is essential for disease prevention and rapid response when confronted with a stroke patient.PurposeThe purpose of this study is to assess stroke knowledge and identify factors associated with awareness among the Iraqi public.Material and methodsA questionnaire-based, cross-sectional survey was conducted on the Iraqi population. The self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Similarly, a comparative study of risk factors in young adults and older adult stroke patients in Sudan reported that arterial hypertension was the dominant risk factor among young adults and the older adult, followed by smoking ( 30 ). As well as previous studies conducted in Lebanon revealed that hypertension and psychological stress were among the most reported risk factors as well ( 28 ), in Jordan ( 8 ), Saudi ( 29 ), UAE ( 26 ), and Iraq ( 27 ).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Similarly, a comparative study of risk factors in young adults and older adult stroke patients in Sudan reported that arterial hypertension was the dominant risk factor among young adults and the older adult, followed by smoking ( 30 ). As well as previous studies conducted in Lebanon revealed that hypertension and psychological stress were among the most reported risk factors as well ( 28 ), in Jordan ( 8 ), Saudi ( 29 ), UAE ( 26 ), and Iraq ( 27 ).…”
Section: Discussionsupporting
confidence: 72%
“…Considering recent studies in the Middle East region to our study results, the aware that stroke is a type of brain disease were various among the participants with the highest in Jordan and Lebanon with more than 95.0% of the participants ( 28 ), then Iraq (92.8%) ( 27 ), Saudi Arabia (89.7%) ( 29 ), and the UAE (70.8%) ( 26 ), while the results of our studies indicated that 93.2% of the participants. In related to the participants’ awareness of stroke is preventable, the results reported by the participants were also various among the countries, with the highest in Iraq (85.6%) ( 27 ), then our Sudan sample with 83.4%, then Jordan and Saudi Arabia with 81.0% ( 8 , 29 ), Lebanon (80.0%) ( 28 ), and the UAE (42.9%) ( 26 ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Generally, and to the best of our knowledge, studies from the Middle East have reported suboptimal levels of knowledge of stroke. Most of the studies from the Middle East have reported inadequate knowledge regarding stroke risk factors and warning symptoms [29][30][31][32][34][35][36] ; on the other hand, only a few studies have reported an adequate level of awareness. [37][38][39] Similarly, studies from different parts of the world have reported an inadequate understanding of stroke in the general population.…”
Section: Discussionmentioning
confidence: 99%